Association of Urbanicity with Schizophrenia and Related Mortality in China: Association de l'urbanicité avec la schizophrénie et la mortalité qui y est reliée en Chine. (April 2021) - Luo, Yanan; Pang, Lihua; Guo, Chao; Zhang, Lei; Zheng, Xiaoying
Objective: Although higher prevalence of schizophrenia in Chinese urban areas was observed, studies focused on the association between schizophrenia and urbanicity were less in China. Using a national representative population-based data set, this study aimed to investigate the relationship between urbanicity and schizophrenia and its related mortality among adults aged 18 years old and above in China. Methods: Data were obtained from the Second China National Sample Survey on Disability in 2006 and follow-up studies from 2007 to 2010 each year. We restricted our analysis to 1, 909, 205 participants aged 18 years or older and the 2, 071 schizophrenia patients with information of survival and all-caused mortality of the follow-up surveys from 2007 to 2010.Schizophrenia was ascertained according to the International Statistical Classification of Diseases, 10th Revision . The degree of urbanicity and the region of residence were used to be the proxies of urbanicity. Of these, the degree of urbanicity measured by the ratio of nonagricultural population to total population and the region of residence measured by six categorical variables (first-tier cities, first-tier city suburbs, second-tier cities, second-tier city suburbs, other city areas, and rural areas). Logistics regression models and restricted polynomial splines were used to examine the linear/nonlinear relationship between urbanicity and the risk of schizophrenia. Cox proportional hazards regression models were used to test the role of urbanicity on mortality risk of schizophrenia patients. Results: 10% increase in the degree of urbanicity was associated with increased risk of schizophrenia ( OR = 1.44; 95% CI, 1.32 to 1.57). The nonlinear model further confirmed the association between the degree of urbanicity and the risk of schizophrenia. This association existed sex difference, as the level of urbanicity increased, schizophrenia risk of males grew faster than the risk of females. The hazard ratio (HR) of mortality in schizophrenia patients decreased with the elevated of urbanicity level, with a HR of 0.42 (95% CI, 0.21 to 0.84). Conclusions: This research suggested that incremental changes in the degree of urbanicity linked to higher risk of schizophrenia, and as the degree of urbanicity elevated, the risk of schizophrenia increased more for men than for women. Additionally, we found that schizophrenia patients in higher degree of urbanicity areas had lower risk of mortality. These findings contributed to the literature on schizophrenia in developing nations under a non-Western context and indicates that strategies to improve mental health conditions are needed in the progress of urbanicity.